Selenium's Significance for Human Health and Its Potential Anti-Oncogenic Properties: A Literature Review - Artur Fabijański; Anna Konarska; Anna Machowiak; Barbara Ufnalska; Justyna Lisiecka; Mateusz Janik; Michał Nowak; Joanna Rychlewska-Duda; Wojciech Firlej; Adriana Dukacz (Journal of Education, Health and Sport)
Introduction